CHALLENGE IN SOCIAL SUPPORT FOR IMPROVING QUALITY OF LIFE PEOPLE WITH HIV/AIDS - ifa roifah; Amar Akbar; Sri Sudarsih (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Background Became HIV-positive people was heavy burden in life, where complex issues always dealt. The complexity of the problem might be faced certainly could impact on the quality of life. One factor that had important role in the quality of life was social support. Objective The aim of this research was to know the correlation between social support and quality of life people with HIV/AIDS, Methods the research design was used correlation analytic with cross sectional approach. The population for this study were all people with HIV/AIDS at KOPENHAM Mojokerto in 2016 who were 79 respondents. The Samples were took by used random sampling which was 65 respondents. The data analysis used coefficient contingency shows p value(0.002) <Î± (0.05), it means there is a relationship of social support with the quality of life people with HIV/AIDS. Results The result of the research showed that 29 respondents who had low quality of life, 20 respondent (69,0%) did not get social support, while from 36 respondent who had high quality of life, 25 (69,4%) respondents get positive social support. Conclusions: Respondents who get social support have high quality of life, caused social support makes people feel appreciated and loved, but there are other factors in quality of life, like age, education level, economy level, marriage status, and gender.